1966
DOI: 10.1103/physrev.147.941
|View full text |Cite
|
Sign up to set email alerts
|

2π0Mass Spectrum and Determination of the Spin of thef0Usinget al.

Abstract: LIFETIME 941 mentum, based upon this procedure, will affect the lifetime by less than 0.2%. VI. CONCLUSIONWe obtain a value for the mean life for K° -> w + ir"~ of n= (0.843±0.013)XlO-10 sec. This result is in agreement with the recently published values of the K%° lifetime given in Table I. T HE properties of the i^-ifi system have been studied using the interaction ir~+p -> ifl+ifl+n at 10 BeV/c. Two enhancements are observed in the TV 0 mass spectrum. The first stretches across the low end of the spectrum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1967
1967
1974
1974

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…8,9 The procedure for the kinematic reconstruction of the 2ir° events using only the directions of the four decay gammas is as described in our previous paper. 1 We have found that this procedure is equivalent to that of Carroll, Middlemas, and Williams, 10 who performed a similar experiment at lower incident momenta. 2 For our data both procedures give the same results.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…8,9 The procedure for the kinematic reconstruction of the 2ir° events using only the directions of the four decay gammas is as described in our previous paper. 1 We have found that this procedure is equivalent to that of Carroll, Middlemas, and Williams, 10 who performed a similar experiment at lower incident momenta. 2 For our data both procedures give the same results.…”
mentioning
confidence: 53%
“…In a previous paper, 1 we reported the observation of two enhancements in the 27r° mass spectrum as seen in the reaction TT" +p~ir° + ir° + n.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…4 " 6 Still others reported broad enhancements of various masses and widths. 7 " 10 The experiments studying 7r + 7r~" interactions are plagued with the proximity of the well-known pwave resonance, the p. Experiments attempting to study 77 0 7r° final states to date fall into two general categories: (1) those in which four y's from the decay of the two neutral pions are observed, affording a poor mass determination, and (2) those in which a good mass determination can be obtained as a residual of either the neutron time of flight or momenta measurements of the charged particles in the final state, thus offering a poor selection for isolating 2ir° states.…”
mentioning
confidence: 99%